Analysis of a Cementless Femoral Stem Neck Fracture Using Scanning Electron Microscopy and the Finite Element Method - Hirokazu Takai; Daisuke Nakayama; Masatoshi Murayama; Tomoki Takahashi (Case Reports in Orthopedics)
Implant fracture is one of the rarest complications of total hip arthroplasty (THA). A 57-year-old woman experienced a fracture of the femoral stem (AHFIX Q, KYOCERA, Japan) about five years after THA. We examined the broken stem by digital microscopy, scanning electron microscopy, and finite element method. The anterolateral corner of the stem’s neck was found to be the origin point of the fracture. Finite element method analysis revealed that the stress concentration was highest in the corner of the hollow for apparatus attachment. The stem’s design has been considered one of the risk factors for stem fracture. In this patient, multiple risk factors, including thin stem (the smallest size, NAR #1), use of the long neck (+3 mm), obesity (body mass index: 27.3), and adjacent osteoarthritis (contralateral THA loosening and knee osteoarthritis), were present. To our knowledge, this is the first reported case of an AHFIX Q stem fracture. Surgeons must keep in mind that fracture of the femoral stem in patients with several risk factors is possible even several years after THA.